Поселенські системи Дніпровського Лісостепового Лівобережжя другої половини VIIІ — середини VІ ст. до н. е. - Гречко, Д.С. (Археологія і давня історія України, 2020)
У статті проведено аналіз поселенських систем
Дніпровського лісостепового Лівобережжя жаботинського періоду та ранньоскіфського часу. Dnieper Left-Bank Forest-Steppe region in the Early
Iron Age was inhabited in several stages. For the
first time, the agricultural population appears in the
Zhabotyn period. Settlements that emerged at this time
would become the centres of some settlement structures
in the Early Scythian period. There are no burial sites
of the settled population of Pre-Scythian times in the
basin of Vorskla and Psel rivers. The few burials of nomads
of Pre-Scythian time are synchronous to this group
of settlements with ashhills. These assemblages, except
Butenky, have no signs of militarization of the population
of the Post-Zrubna culture, which have left in the Forest-
Steppe. It’s likely that these two groups of populations coexisted
peacefully, occupying separate ecological niches.